Organic and Multicultural Ways of Reading Bulosan - Streamas, John (Archīum Ateneo, 2024)
This essay argues that students in introductory classes read America Is in the Heart more perceptively than most professional “multicultural” critics. Students’ indifference to the book’s genre, for example, allows them to see clearly the meaning and value of its Part One, and to read the closing paragraph not as a postmodern refusal of closure but as a step on the way toward reconciling “America” with the work of “becoming Filipino.” Such engagement with the book is an example of “organic” reading.